Air pollution and the forests of developing and rapidly industrializing regions : Report No. 4 of the IUFRO Task Force on Environmental Change (IUFRO research series ;, 2000)
This book examines the importance of air pollution for the forests of rapidly industrializing countries and regions in 12 main chapters contributed by different authors. Its geographical coverage includes South and Central America, Africa and Asia, including Siberia, China and Korea. The problems presented by air pollution are placed within the more general context of sustainable development within these regions and the historical legacy that they are attempting to deal with. Attention is drawn to the very serious problems associated with poor air quality in cities such as Mexico City and Chongqing, China. Air pollution in these areas is amongst the worst in the world. Several chapters examine the importance of forest fires as a source of air pollution, with particular reference being made to the Southeast Asian fires in recent years. The available information about the effects of this pollution on the surrounding forests is reviewed, and recommendations are made for a better understanding of the impacts. The final main chapter of the book reviews recent developments in air pollution control policies in the different regions covered. This chapter is followed by conclusions (by the editors) and a subject index. The book is of interest to postgraduates and researchers in forestry, pollution studies and environmental science. The 12 main chapters of the book are all noticed separately on the CAB ABSTRACTS database.